2005
DOI: 10.2298/bah0502035t
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Bulgarian livestock genetic resources: 1. Genetic diversity in Bulgarian grey cattle as revealed by microsatellite markers

Abstract: nema

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Comparisons of H E and PIC of Curraleiro Pé-Duro breed in relation to other breeds that were studied using some microsatellite loci in common with this study showed similar findings in Creole (Steigleder et al, 2004) and Grey (Teneva et al, 2005) breeds. An exception was found for the TGLA122 locus, which showed a higher PIC in Curraleiro Pé-Duro.…”
Section: Discussionsupporting
confidence: 85%
“…Comparisons of H E and PIC of Curraleiro Pé-Duro breed in relation to other breeds that were studied using some microsatellite loci in common with this study showed similar findings in Creole (Steigleder et al, 2004) and Grey (Teneva et al, 2005) breeds. An exception was found for the TGLA122 locus, which showed a higher PIC in Curraleiro Pé-Duro.…”
Section: Discussionsupporting
confidence: 85%
“…For example, in a study of 35 Bulgarian Grey cattle the same loci were involved and 83 alleles were determined in total with an average 7.6 alleles per locus. The large number of alleles were determined at loci TGLA227 and TGLA53 (12 alleles), and lowest number at locus BM1824 (4 alleles) with equally high polymorphism detected at loci ETH3, BM2113 and ETH225, [18]. A similar study in Romania determined 125 different alleles in 5 different cattle breeds.…”
Section: Discussionmentioning
confidence: 83%
“…The first one is described in our previous study (Teneva et al, 2005). The other -Rhodope Shorthorn local cattle breed is dispersed in the Rhodope Mountains.…”
Section: Bulgarian Local Cattle Breedsmentioning
confidence: 99%
“…After the Information of EAAP-Animal genetic data bank of the European Association for Animal Production /http://www.tiho-hannover.de/einricht/zucht/eaap/ the status of endangerment of this breed is "critically endangered" (NFN =75). For the Grey cattle the status was described in our previous study (Teneva et al, 2005).…”
Section: Bulgarian Local Cattle Breedsmentioning
confidence: 99%
See 1 more Smart Citation